Energy-related financial literacy among university students - Hernández-Mejía, Sergio; Moreno-García, Elena (RAN - Revista Academia & Negocios, 2025)
Purpose: To analyze energy and financial literacy among university students in Veracruz, Mexico and its impact on investment decisions regarding energy-efficient appliances. Methodology: The data were obtained by applying a structured survey to a non-probability self-selected sample. A multiple regression model and a Probit model were employed to analyze data from 557 students. Results: Financial and energy literacy, as well as students’ area of knowledge, have a significant impact on their ability to make decisions about energy-efficient appliances. Implications: Education on basic energy and on financial topics can improve students’ decision-making ability regarding energy-efficient appliances. This enhances financial well-being and contributes to environmental conservation. Future research should analyze other variables, such as income level, work experience, and socialization on energy and financial practices. Originality: This is the first study conducted in Latin America to examine energy investment literacy determinants. The results may contribute to the design of educational strategies to improve young people’s energy investment decision-making.